Octopus‐Inspired Soft Arm with Suction Cups for Enhanced Grasping Tasks in Confined Environments. (29th August 2019) - Mazzolai, Barbara; Mondini, Alessio; Tramacere, Francesca; Riccomi, Gianluca; Sadeghi, Ali; Giordano, Goffredo; Del Dottore, Emanuela; Scaccia, Massimiliano; Zampato, Massimo; Carminati, Stefano
Abstract : Octopuses have impressive manipulation capabilities empowered by the intrinsic adaptation of their soft arms combined with distributed suckers. Drawing inspiration from the arm morphology and abilities of the octopus, the integrated design of a conical soft robotic arm endowed with suction cups is presented herein. The proposed arm exploits soft robotic technologies as in materials (combining stiff and soft silicones) and actuation (tendons to drive motion and fluidic channels for suction cup actuation) for retrieving objects in confined spaces of unknown shapes and sizes. The soft arm is able to grasp varied and complex‐shaped objects, to move in air, water, and oil, and to retrieve items immersed in a 70 mm diameter pipe, under pressure (up to 18 bar). Suction cups enable the arm to retrieve objects that would be impossible to grasp without them and help in improving the grasping force up to ≈1.4 times in air, ≈2.4 times in water, and ≈12.5 times in oil. The enhanced holding force (up to 3.3 N, ≈3.9 times arm weight) and a wide spectrum of objects negotiable by the arm make it a universal tool for object retrieval in confined spaces and wet conditions. Abstract : The intrinsic adaptation of soft materials coupled with the attachment properties of suction cups enables new grasping abilities in soft robotic arms, improving holding force and expanding the spectrum of objects that can be retrieved in confined spaces and in harsh environments.